(untitled) (Iraqi Journal of Civil Engineering, 2010)
AbstractDeflection of partially prestressed concrete beams is investigated using the finite element method taking in to account the plasticity of steel, nonlinearity of concrete in compression and tension softening of concrete. Embedded bar approach is used to represent the steel reinforcement and prestressing tendon in concrete layer. Elastic perfectly-plastic approach has been employed to model the compressive behaviour of the concrete.The yield condition is formulated in terms of the first two-stress invariants. The movement of the subsequent loading surfaces is controlled by the hardening rule, which is extrapolated from the uniaxial stress-strain relationship defined by a parabolic function. Concrete crushing is a strain controlled phenomenon, and can be monitored by a fracture surface similar to the yield surface. A smeared fixed crack approach is used to model the behaviour of the cracked concrete, with a tensile strength criterion to predict crack initiation. The steel is considered as an elastic perfectly plastic material with linear strain hardening, steel reinforcement is assumed to have similar tensile and compressive stress-strain relationship. The calculated and the observed effects have shown a satisfactory agreement compared with experimental results.